2015
DOI: 10.1109/tse.2014.2369047
|View full text |Cite
|
Sign up to set email alerts
|

Using Declarative Specification to Improve the Understanding, Extensibility, and Comparison of Model-Inference Algorithms

Abstract: Abstract-It is a staple development practice to log system behavior. Numerous powerful model-inference algorithms have been proposed to aid developers in log analysis and system understanding. Unfortunately, existing algorithms are typically declared procedurally, making them difficult to understand, extend, and compare. This paper presents InvariMint, an approach to specify modelinference algorithms declaratively. We applied the InvariMint declarative approach to two model-inference algorithms. The evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…Notice that the model inferred by traditional 2-tails (in Figure 1) accepts T1, T4, T7, but not T2, T3, T5, T6, and T8. This model is 1 Modal Transition System restricted to accepting traces that contain no repetitions of any methods. On the other hand, the CONTRACTOR++ model (in Figure 2) is less restrictive, as it accepts T1, T2, T4, T7, T8, but not T3, T5, T6.…”
Section: Idmentioning
confidence: 99%
See 3 more Smart Citations
“…Notice that the model inferred by traditional 2-tails (in Figure 1) accepts T1, T4, T7, but not T2, T3, T5, T6, and T8. This model is 1 Modal Transition System restricted to accepting traces that contain no repetitions of any methods. On the other hand, the CONTRACTOR++ model (in Figure 2) is less restrictive, as it accepts T1, T2, T4, T7, T8, but not T3, T5, T6.…”
Section: Idmentioning
confidence: 99%
“…Another two templates (i.e., never followed by, and never immediately followed by) were introduced by Beschastnikh et al [1] and have been demonstrated to be useful for describing FSA mining algorithms. The last two templates (i.e., always immediately followed by, and always immediately precedes) are newly introduced in this work.…”
Section: B Model Fissionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such approaches have traditionally been concerned with the inference of conventional Finite State Machines from traces [7], [8], [9], [10], [11], [12], [13]. Recently, however, several attempts have been made to infer Extended Finite State Machines (EFSMs [14]).…”
Section: Introductionmentioning
confidence: 99%